2022
DOI: 10.1038/s41598-022-19514-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual body-representation on motor skill learning

Abstract: Motor learning is often hindered or facilitated by visual information from one’s body and its movement. However, it is unclear whether visual representation of the body itself facilitates motor learning. Thus, we tested the effects of virtual body-representation on motor learning through a virtual reality rotary pursuit task. In the task, visual feedback on participants’ movements was identical, but virtual body-representation differed by dividing the experimental conditions into three conditions: non-avatar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Generally, these findings align with previous literature where anthropomorphic-like displays aided the perception of motion features, when compared to reduced motion versions [24,35,38,48,51]. Atkinson and colleagues [48] found that emotion classification accuracy from body expression was improved in video in relation to PL, and that movement exaggeration exponentiated accuracy levels for some emotions.…”
Section: Plos Onesupporting
confidence: 86%
See 3 more Smart Citations
“…Generally, these findings align with previous literature where anthropomorphic-like displays aided the perception of motion features, when compared to reduced motion versions [24,35,38,48,51]. Atkinson and colleagues [48] found that emotion classification accuracy from body expression was improved in video in relation to PL, and that movement exaggeration exponentiated accuracy levels for some emotions.…”
Section: Plos Onesupporting
confidence: 86%
“…Narang and colleagues [24] found that self-recognition of motion was better with realistic 3D avatars than PL, while motion recognition of others was better with PL. Further, a recent VR study by Shin and colleagues [51] compared the effect of a hand-shaped avatar, a non-hand shaped avatar and no avatar in a motor learning task, confirming that the learning rate was facilitated by recognizing one's body form. This perspective is also reinforced by multiple studies in the field of human-computer interaction, where it is well established that animated characters influence how people engage with and perceive virtual environments [41,[52][53][54].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, like VR, Immersive VR (IVR) allows the creation of highly personalized virtual environments (VE) with an adaptable number of visual feedback elements. In immersive VE, the use of avatars for self-representation is common and may have an important impact on user perception [55], interaction within the VE [56], and motor learning [57]. The use of avatars can allow for the visualization of one's movements in real-time and has been implemented throughout various studies to teach movements by imitation learning [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%